2023
DOI: 10.1002/ctm2.1258
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cardiac MicroRNAs safeguard against dilated cardiomyopathy

Abstract: Background Cardiac‐resident or ‐enriched microRNAs (miRNAs) could be released into the bloodstream becoming circulating cardiac miRNAs, which are increasingly recognized as non‐invasive and accessible biomarkers of multiple heart diseases. However, dilated cardiomyopathy (DCM)‐associated circulating miRNAs (DACMs) and their roles in DCM pathogenesis remain largely unexplored. Methods Two human cohorts, consisting of healthy individuals and DCM patients, were enrolled for serum miRNA sequencing (10 vs. 10) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The specific mechanism remains to be further researched. The role of miR-26a-5p on cardiac hypertrophy has been elucidated in many studies [ 15 , 34 36 ], and its mechanism may be related to the regulation of autophagy. Therefore, we constructed cell and animal cardiac hypertrophy models to explore whether miR-26a-5p could regulate autophagy, activate inflammasomes and lead to the aggravation of pathological cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanism remains to be further researched. The role of miR-26a-5p on cardiac hypertrophy has been elucidated in many studies [ 15 , 34 36 ], and its mechanism may be related to the regulation of autophagy. Therefore, we constructed cell and animal cardiac hypertrophy models to explore whether miR-26a-5p could regulate autophagy, activate inflammasomes and lead to the aggravation of pathological cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Its downregulation would lead to sarcomere dysfunction and, in turn, cardiac remodeling. In addition, there is evidence that MYH6 regulation of a miRNA-FOXO3 axis plays a key role in preventing myocardial apoptosis and excessive autophagy during the pathogenesis of DCM ( Cheng et al, 2023 ). It has been reported that the mutation of MYH6 can lead to arrhythmia and sudden cardiac death in DCM( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The speci c mechanism remains to be further researched. The role of miR-26a-5p on cardiac hypertrophy has been elucidated in many studies [15,[34][35][36] , and its mechanism may be related to the regulation of autophagy. Therefore, we constructed cell and animal cardiac hypertrophy models to explore whether miR-26a-5p could regulate autophagy, activate in ammasomes and lead to the aggravation of pathological cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%